NPK-lannoituksen vaikutus Pito-perunan ravinteiden ottoon - Varis, Eero (Agricultural and Food Science, 1973)
The effects of N rates of 0, 100 and 200, P rates of 0, 87 and 174 and K rates of 0, 166 and 332 kg/ha on the nutrient uptake of Pito potato was studied in 1967, 1968 and 1970. The highest yield of tuber dry matter, 5 793 kg/ha, was obtained at the N1P2 level, the effect of K being insignificant. The corresponding total dry matter yield was 8 016 kg/ha. In this case, the total uptakes of nutrients were (kg/ha) 129 N, 15 P, 230 K, 42 Ca and 19 Mg. Corresponding uptakes in the tubers were 75 N, 11 P, 122 K, 2.2 Ca and 6 Mg. N application increased the N uptake by increasing the dry matter yield and improving the N content of the haulms and the tubers. The effect was more pronounced in the case of the haulms. Uptakes of P, K, Ca and Mg also increased. The relative uptake of P and Mg decreased, however, and their transfer into tubers was delayed. The K content of the haulms increased, their Ca content decreased. P application increased the uptake of N, K, Ca and Mg in accordance with the increase of dry matter. The transfer of N and Ca into the tubers was accelerated, that of K retarded by the end of the growing period. K application had no significant effect on the uptake of N, P, or K. However, the uptake of P was retarded by a heavy KN application. The uptake of Ca showed an insignificant decreasing trend. The uptake of Mg and the Mg content of the haulms decreased somewhat. The K content of the haulms and also of the tubers was improved.